THE EFFECT OF THE PROJECT BASED LEARNING (PjBL) MODEL ON THE LEARNING OUTCOMES OF STUDENTS OF PUBLIC ELEMENTARY SCHOOL 141 PEKANBARU - Asnita; Laili Rahmi (SOSIOEDUKASI, 2026)
The use of less diverse and teacher-centered teaching methods frequently explains students' poor learning outcomes concerning Indonesian cultural diversity in primary education. This research seeks to ascertain how fourth-grade pupils at SD Negeri 141 Pekanbaru acquire knowledge through the Project Based Learning (PjBL) approach. This research used a quasi-experimental design with a non-equivalent control group. The 35 students in the research sample were divided into two groups: the experimental class, which had 17 students utilising the PjBL methodology, and the control class, which had 18 students using conventional teaching methods. Pretests and posttests that assessed cognitive learning outcomes were used to collect data. An independent samples t-test was used to analyse the data after the completion of the required tests for homogeneity and normality. According to the study, the experimental group's average posttest score was 83.82, significantly higher than the control group's score of 58.89. The results of the hypothesis test showed that Ha was accepted and H0 was rejected, with a significance value (Sig. 2-tailed) of 0.000 being less than 0.05. The research finds that the Project Based Learning (PjBL) approach greatly improves student learning results. This approach has successfully improved student involvement and understanding of academics via hands-on project tasks.